Opioid Antagonists: Will they Solve all of the Problems Associated with Opioid Agonists? - Adam M Kaye (Global Journal of Anesthesiology - Peertechz Publications, 2014)
Physicians employed in operating and emergency rooms have utilized opioid antagonist for almost half a century for the treatment of opioid overdose. The prototype antagonist remainsnaloxone hydrochloride, which actually received FDA approval back in 1971. Why after so many years on the market is this medication now being formulated in the form of an easy to use "auto-injector" that was designed for non-medical professionals to be able to utilize at a moment's notice? Could this wonder product, being hailed as the best possible safety tool available for life threatening opioid emergencies actual make hero's out of lay people? [1].